Gino Germani, Autoritarismo, fascismo y populismo nacional, Buenos Aires, Temas, 2003, 306 pp - Rosa, María Fernanda de la (2004)
Fil: Rosa, María Fernanda de la. Pontificia Universidad Católica Argentina; Argentina